Chronic exposure to stress hormones alters the subtype of store‐operated channels expressed in H19‐7 hippocampal neuronal cells. Issue 6 (25th February 2013) - Piron, Matthew; Villereal, Mitchel L.
Abstract Differentiating H19‐7 hippocampal precursor cells up‐regulate (∼4.3‐fold) store‐operated channel (SOC) activity; relatively linear current‐voltage curves indicate an ISOC subtype of SOC. In differentiated H19‐7 neurons, the majority of agonist (arginine vasopressin, AVP)‐stimulated Ca2+ entry occurs via SOCs, based on 2‐aminoethyldiphenylborinate (2‐APB) inhibition data and the observation that transient receptor potential C1 (TRPC1) channel knock down cells show a dramatic reduction of thapsigargin‐stimulated store‐operated Ca2+ entry (SOCE) and inhibition of AVP‐stimulated Ca2+ entry. Treatment of H19‐7 cells with the rat stress hormone corticosterone during differentiation induces a significant increase in AVP‐stimulated Ca2+ entry, which is virtually eliminated by 2‐APB, suggesting a corticosterone‐induced increase of SOCE. Corticosterone also enhances AVP‐stimulated Mn2+ entry, confirming an elevated Ca2+ entry pathway, rather than a decreased Ca2+ extrusion. When corticosterone addition is delayed until after H19‐7 cells have fully differentiated, it still elevates SOCE. In corticosterone‐treated H19‐7 cells, the knock down of TRPC1 no longer blocks thapsigargin‐stimulated Ca2+ entry suggesting that the subtype of SOCs expressed in H19‐7 cells is altered by corticosterone treatment. Electrophysiological studies demonstrate that store‐operated currents in corticosterone‐treated H19‐7 cells exhibit a highly inward rectifying current‐voltage curve consistent with an ICRAC subtype of SOCs. Consistent with this finding is the observation that corticosterone treatment of H19‐7 cells increases the expression of the ICRAC channel subunit Orai1. Thus, the subtype of SOCs expressed in H19‐7 hippocampal neurons can be altered from ISOC to ICRAC by chronic treatment with stress hormones. J. Cell. Physiol. 228: 1332–1343, 2013. © 2012 Wiley Periodicals, Inc.